2000
DOI: 10.1021/bi991447r
|View full text |Cite
|
Sign up to set email alerts
|

Fibrils Formed in Vitro from α-Synuclein and Two Mutant Forms Linked to Parkinson's Disease are Typical Amyloid

Abstract: Two missense mutations in the gene encoding alpha-synuclein have been linked to rare, early-onset forms of Parkinson's disease (PD). These forms of PD, as well as the common idiopathic form, are characterized by the presence of cytoplasmic neuronal deposits, called Lewy bodies, in the affected region of the brain. Lewy bodies contain alpha-synuclein in a form that resembles fibrillar Abeta derived from Alzheimer's disease (AD) amyloid plaques. One of the mutant forms of alpha-synuclein (A53T) fibrillizes more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
652
1
11

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 751 publications
(720 citation statements)
references
References 75 publications
56
652
1
11
Order By: Relevance
“…It is apparent that the type 2 aggregates observed resemble α-Syn fibrils grown at high bulk concentrations in solution, which typically show a variable and stochastic lag phase followed by a rapid elongation process. 7,13,14,50,60 Elongated, linear, or dendrite-like fibrils of length up to several micrometers were frequently reported in the context of α-Syn fibrillation. 7,13,14,50 In addition, aggregation mechanisms for amyloidogenic proteins at interfaces in agreement with our observations are comprehensively described in the literature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is apparent that the type 2 aggregates observed resemble α-Syn fibrils grown at high bulk concentrations in solution, which typically show a variable and stochastic lag phase followed by a rapid elongation process. 7,13,14,50,60 Elongated, linear, or dendrite-like fibrils of length up to several micrometers were frequently reported in the context of α-Syn fibrillation. 7,13,14,50 In addition, aggregation mechanisms for amyloidogenic proteins at interfaces in agreement with our observations are comprehensively described in the literature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…7,13,14,50,60 Elongated, linear, or dendrite-like fibrils of length up to several micrometers were frequently reported in the context of α-Syn fibrillation. 7,13,14,50 In addition, aggregation mechanisms for amyloidogenic proteins at interfaces in agreement with our observations are comprehensively described in the literature. 61,62 For instance, Zhu et al reported two distinct onsurface aggregation mechanisms for the amyloidogenic protein SMA predominantly differing in their growth rates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tight linkage of disaggregation and proteolysis may be due to a physical linkage of proteins or protein complexes that carry out these activities. Additionally, because amyloid is known to be protease resistant, [39][40][41] it is likely that disaggregation is required for proteolysis, and this relationship would necessitate a linear correlation between disaggregation and proteolysis (Fig. 7).…”
Section: Mammalian Amyloid Disaggregase and Proteolysis Activities Armentioning
confidence: 99%
“…Recombinant, human wild-type α-synuclein was produced in E. coli and purified as described previously [35,36]. The lyophilized protein was dissolved in 10 mM sodium phosphate buffer (pH 7.0) with 100 mM NaCl and filtered through a 0.22 μm nylon spin filter (Costar) to remove high-molecular mass aggregates.…”
Section: Purification and Oxidation Of Recombinant α-Synucleinmentioning
confidence: 99%